Non‐Pecuniary Rewards, Multiple Job‐Holding and the Labour Supply of Creative Workers: The Case of Book Authors*. Issue 316 (13th December 2020) - Longden, Thomas; Throsby, David
Abstract : Non‐pecuniary rewards to work, or psychic income, are a pervasive phenomenon in several labour markets, yet they have been little investigated either theoretically or empirically. Creative industries are a particular case where non‐monetary incentives are widely observed. These are also industries where moonlighting commonly occurs because artistic or creative activity is generally low paid, such that workers have to balance their chosen pursuit with another job to make ends meet. In this paper we propose a labour supply model that accounts for the psychic income derived from creative work, monetary remuneration and heterogeneity between occupations in a multiple job‐holding context. The model is estimated using three‐stage least squares, allowing us to control for simultaneity bias due to the constraint of time and the tendency for multiple job‐holdings. We estimate the model using data from a survey of Australian book authors. The use of a proxy for psychic income, measured as the disparity between an author's monetary compensation and a shadow price of labour, enables us to gauge the effects of non‐pecuniary benefits on the labour supply decisions of this type of creative worker.